Utdanning i kunstfag Samarbeid, kvalitet og spenninger - Bandlien, Bjørn-Terje; Olaussen, Ingvild Olsen; Letnes, Mari-Ann; Angelo, Elin (MusPed:Research, 2021)
This anthology presents research projects that examine the quality and tension in various forms of collaboration on teaching in and across different artistic disciplines, art forms and educational programs. The contributors are teachers, administrators, and researchers from Norway's 'culture school', primary school and preschool as well as higher educational programs that train teachers for these schools. Data for the studies has been obtained from these types of schools and from joint projects between them. The research spans a number of topics: culture school's external and internal collaboration patterns, diversity, well-being, tensions and conflicts in collaboration between culture school and primary school, what happens in practice when differing views about art collide, challenges that German music teachers encounter in teaching music at the primary school level, collaboration between students and children on musical theater productions, a statistical analysis of the elective primary school subject 'theater production', a look at how performative and transformative pedagogical practices with resistance, disruption, and transgression as key aspects can lead to understandings of difference and the bizarre. The book also includes an overview of the considerable research on collaboration between music schools and primary schools in Germany in connection with the project 'Jedem Kind ein Instrument' (An Instrument for Every Child). This anthology provides a substantial contribution to research on culture school in particular, inasmuch as culture school is a part of so many different realms of collaboration. The idea for this anthology was conceived in a music pedagogical research environment that, in keeping with the focus on collaboration, sought to encompass the full breadth of different artistic disciplines, art forms and educational programs.